Answer:
13/4
Step-by-step explanation:
Answer:
(-4,-3)
Step-by-step explanation:
just use rise and run slope
you run-4 units x and rise y -3
The value of x in the equation a – bx = cx + d is = a - d / c + b
The value of x in the equation 5 – 6x = 8x + 17 is - 6 / 7
a - bx = cx + d
add bx to both sides of the equation
a - bx + bx = cx + bx + d
a = cx + bx + d
subtract d form both sides of the equation
a - d = cx + bx + d - d
a - d = cx + bx
using distributive law on the right side of the equation
a - d = x (c + b)
divide both sides by (c + b)
Therefore,
x = a - d / c + b
Let's use the same method to solve 5 – 6x = 8x + 17
5 – 6x = 8x + 17
add 6x to both sides
5 – 6x + 6x= 8x + 6x + 17
5 = 14x + 17
subtract 17 from both sides
5 - 17 = 14x + 17 - 17
-12 = 14x
divide both sides by 14
x = -12 / 14
x = - 6 / 7
learn more on equations here: brainly.com/question/7838122
Answer: 4th box
Step-by-step explanation:
Answer: see proof below
Step-by-step explanation:
Use the Power Reducing Identity: sin² Ф = (1 - cos 2Ф)/2
Use the Double Angle Identity: sin 2Ф = 2 sin Ф · cos Ф
Use the following Sum to Product Identities:
Proof LHS → RHS
LHS = RHS: tan (A + B) = tan (A + B)
We know that,
___________________________________
Now, Let's solve !
Answer:
The answer of this equation is:
1.9